Pollen fertility assessments on selected diploid genotypes of musa species in the IITA breeding collection - Taiwo, T.O. (University of Ibadan, 2023)
Breeding of all types of bananas including plantain is dependent on the development of superior diploids with disease and pest resistance and better quality to be used as male parents. There has been a major challenge over the years on the selection of diploid parents with desirable traits for plantain breeding. Twenty-one diploid cultivars and hybrids in the International Institute of Tropical Agriculture musa germplasm collection were evaluated for male fertility to determine their suitability for use in hybridizations for plantain improvement. Pollen viability was assessed through staining with 2 3 5- triphenyl tetrazolium chloride and in vitro pollen germination on diploids, and the effect of number of male flower and anther size on pollen quantity was investigated, the genotype with the highest rating for percentage viability through staining was recorded in SH3362 (78.66%) and the lowest was recorded in Gu-nin-chio (0.41%) while Beram, Kasaska, Pari Jari Buaya and Morong Princessa has (0%). The highest pollen tube length among the twenty-one diploid genotype was 1448-1 (3024.1 µm) while the lowest pollen tube length was Yangambi (232.60 µm) and Beram, Kasaska, P. Jari Buaya and Morong princessa had no tube growth. The number of male flower and anthers length directly influence the quantity of pollen while anther width has no significant effect on pollen quantity. From the study, pollen viability via staining was correlated with the in vitro pollen germination and there was positive correlation between viable pollen and pollen tube growth, while viable pollen and pollen tube growth both has negative correlation on number of male flower and anther length and width for genotypes tested. 10 fertile lines for use in breeding from the observed genotypes were identified (1448-1, 2829-62, 8075-7, 9128-3, Awondaeke, Bieyeng, Calcutta 4, Higa, SH-3362 and Padri). This research work will help to identify genotypes for use as parents for plantain breeding, help to solve the problem of poor hybrid production due to low fertility, and help in successful implementation of breeding programs and ensure safe hybridizations